Synergistic Action of Dendritic Mitochondria and Creatine Kinase Maintains ATP Homeostasis and Actin Dynamics in Growing Neuronal Dendrites - Fukumitsu, Kansai (J Neurosci, 2015)
The distribution of mitochondria within mature, differentiated neurons is clearly adapted to their regional physiological needs and can be perturbed under various pathological conditions, but the function of mitochondria in developing neurons has been less well studied. We have studied mitochondrial distribution within developing mouse cerebellar Purkinje cells and have found that active delivery of mitochondria into their dendrites is a prerequisite for proper dendritic outgrowth. Even when mitochondria in the Purkinje cell bodies are functioning normally, interrupting the transport of mitochondria into their dendrites severely disturbs dendritic growth. Additionally, we find that the growth of atrophic dendrites lacking mitochondria can be rescued by activating ATP-phosphocreatine exchange mediated by creatine kinase (CK). Conversely, inhibiting cytosolic CKs decreases dendritic ATP levels and also disrupts dendrite development. Mechanistically, this energy depletion appears to perturb normal actin dynamics and enhance the aggregation of cofilin within growing dendrites, reminiscent of what occurs in neurons overexpressing the dephosphorylated form of cofilin. These results suggest that local ATP synthesis by dendritic mitochondria and ATP-phosphocreatine exchange act synergistically to sustain the cytoskeletal dynamics necessary for dendritic development.